OPTIMALISASI FUNGSI LABORATORIUM KONSELING SEBAGAI PENUNJANG KOMPETENSI MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING ISLAM - Zaini Mufidah; Muh. Wasith Achadi; Alfin Miftahul Khairi (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2022)
The aim of this research is to provide an ideal picture of a counseling laboratory so that its use is more optimal. This research method uses qualitative methods. The research location is the Counseling Laboratory, Islamic Guidance and Counseling Study Program, Faculty of Ushuluddin and Da'wah, UIN Raden Mas Said Surakarta. The results of this research show that the condition of the Counseling Laboratory is quite optimal in its development and use to develop students' abilities in theoretical and practical da'wah activities that prioritize Islamic values in the counseling process. However, it still needs to be maximized in terms of funding and infrastructure, and all activities carried out must be documented neatly and completely, so that the function and benefits of the Counseling Laboratory as a place to hone student competencies in the field of counseling can be used optimally.